Possibilities and perspectives of remote work of courts of Lithuania - Malakauskas, Arnas; Matulytė, Raminta (Vilnius University Open Series, 2021)
This article analyses the topic of opportunities and perspectives of remote proceedings of the courts of Lithuania. Based on international documents, legal acts and legal doctrine, information provided by the National Courts Administration, interviews with judges and attorneys, the situation of remote criminal proceedings in the context of the COVID-19 pandemic is presented. An analysis of the impact of remote proceedings of courts on the rights and obligations of participants in criminal proceedings was also performed. This article provides insights into the legal regulation and practice of remote proceedings of courts in the future.